Advances in research on Rotavin-M1 - Thi Luan Le; Van Man Nguyen; Thuy Huong Nguyen; Duc Anh Dang; Van Trang Nguyen; Bich Hanh Tran; Thi Giang Huong Tran; Thi Oanh Tran; Gia Khanh Pham; Baoming Jiang; Roger Glass; Duncan Steel; et al. (Vietnam Journal of Science, Technology and Engineering, 2017)
“Rotavin-M1” is an oral live-attenuated vaccine that prevents diarrhea in children under five years old, produced from rotavirus strains G1P [1] on Vero cells. This vaccine has been studied for 16 years beginning with monitoring the local circulating strain and eventually establishing a seed lots system. The safety and immunogenicity of the vaccine were found equivalent to internationallyimported vaccines.